Medical Bondage Race, Gender, and the Origins of American Gynecology - Owens, Deirdre Cooper (University of Georgia Press, 2017)
Medical Bondage explores how, in the nineteenth century, experimental surgeries on enslaved and laboring women enabled the rise of American gynecology as a medical specialty, and shaped our understanding of race. Merging women's, medical, and social history, the book makes Black and Irish women's lives-not just their bodies-part of an origins story of American medicine (one that has largely been told with an exclusive focus on white male historical actors).
Description based on print version record.
KU Select 2017: Front list Collection
Keywords: Social Science / Women's Studies; Medical / Gynecology & Obstetrics; Medicine; Electronic books